2007
DOI: 10.1002/ccd.21418
|View full text |Cite
|
Sign up to set email alerts
|

First direct in vivo comparison of two commercially available three‐dimensional quantitative coronary angiography systems

Abstract: Aim: The in vivo comparison of the accuracy of two 3-dimensional quantitative coronary angiography (QCA) systems. Methods: Precision-drilled plexiglass phantoms with five different luminal diameters (0.5-1.9 mm) were percutaneously inserted into the coronary arteries of four Yorkshire pigs. Twenty-one angiographic images of these stenotic phantoms were acquired for in vivo validation testing. Quantitative assessments of the minimum, maximum, and mean luminal diameters together with the minimum luminal area wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
(15 reference statements)
4
19
0
Order By: Relevance
“…more precise stent selection, tackling chronic total occlusions, remote or robotic guidance of PCI). But only recently have the advances in computer power made simple and fast 3-dimensional rendering of angiographic images possible [6][7][8][9][10]. Three-dimensional angiography proved useful in assessment of one of the most complex interventional challenges, left main coronary anatomy [20].…”
Section: Analityków (Zmienność Pomiędzy Obserwatorami) Wykres Ilustrmentioning
confidence: 99%
See 1 more Smart Citation
“…more precise stent selection, tackling chronic total occlusions, remote or robotic guidance of PCI). But only recently have the advances in computer power made simple and fast 3-dimensional rendering of angiographic images possible [6][7][8][9][10]. Three-dimensional angiography proved useful in assessment of one of the most complex interventional challenges, left main coronary anatomy [20].…”
Section: Analityków (Zmienność Pomiędzy Obserwatorami) Wykres Ilustrmentioning
confidence: 99%
“…Although 2D QCA has been well validated in phantoms and its reproducibility is well established, foreshortening of the arterial segment of interest in a two-dimensional image continues to be a significant problem when determining lesion length, eccentricity, and tortuosity [2,3]. Due to these limitations, coronary angiography modeling using threedimensional QCA on the basis of images and structures visualized and captured during standard and rotational angiography was introduced [4,5] and is currently being evaluated for its utility in clinical practice [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the systems differ in their calibration methods. CardiOp-B requires the operator to input the size of the catheter in the image into the program, whereas the Medis and CAAS 5 systems automatically calibrates the images using DICOM (Digital Imaging and Communications in Medicine) information embedded in the angiographic images (Gradaus et al, 2006;Ramcharitar et al, 2008a). Once the image is created, operators can manipulate the images by zooming in or rotating the image.…”
Section: Three-dimensional Qcamentioning
confidence: 99%
“…However, comparisons of 3D QCA programs to conventional 2D QCA programs have shown mixed results regarding the accuracy of this technology (Ramcharitar www.intechopen.com et al, 2008a;Dvir et al, 2005;Tsuchida et al, 2007;Meerkin et al, 2010;Wellnhofer et al, 1999;Tu et al, 2010). One small study has compared the two current 3D QCA programs using phantom models demonstrated that the CAAS 5 system may be more accurate than the CardiOp-B system (Ramcharitar et al, 2008a). …”
Section: Three-dimensional Qcamentioning
confidence: 99%
“…With the development of Computed Tomography (CT), MRI angiography and rotational angiography, patient-specific 3D geometries of coronary arteries are readily available for studies of hemodynamics and resulted in a number of recently published researches (Ramcharitar et al, 2008;Gijsen et al, 2008;van der Giessen et al, 2009;Goubergrits et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%